2007
DOI: 10.1103/physrevlett.98.095503
|View full text |Cite
|
Sign up to set email alerts
|

Vibrational Properties of Hexagonal Boron Nitride: Inelastic X-Ray Scattering andAb InitioCalculations

Abstract: The phonon dispersion relations of bulk hexagonal boron nitride have been determined from inelastic x-ray scattering measurements and analyzed by ab initio calculations. Experimental data and calculations show an outstanding agreement and reconcile the controversies raised by recent experimental data obtained by electron-energy loss spectroscopy and second-order Raman scattering. DOI: 10.1103/PhysRevLett.98.095503 PACS numbers: 63.20.Dj, 61.10.Eq, 63.10.+a, 71.15.Mb Besides their intermediate structure bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

43
214
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 223 publications
(262 citation statements)
references
References 31 publications
43
214
3
Order By: Relevance
“…[4,6], the five phonon replicas at 5.76, 5.79, 5.86, 5.89, and 5.93 eV had been labeled LO, TO, LA, TA, and ZA, respectively, following the study of the vibrational properties in hBN reported in Ref. [7]. The more detailed study of the hBN phonon dispersion performed in Ref.…”
Section: B Resultsmentioning
confidence: 99%
“…[4,6], the five phonon replicas at 5.76, 5.79, 5.86, 5.89, and 5.93 eV had been labeled LO, TO, LA, TA, and ZA, respectively, following the study of the vibrational properties in hBN reported in Ref. [7]. The more detailed study of the hBN phonon dispersion performed in Ref.…”
Section: B Resultsmentioning
confidence: 99%
“…The Raman-allowed hBN phonon mode is the E 2g mode at 1,367 cm −1 (refs 26,27 Fig. 2b) is not Raman active, and thus is completely absent in the Raman measurement of pristine hBN 27 . The red curve in Fig.…”
mentioning
confidence: 99%
“…Very large electron-phonon interaction in h-BN has been previously inferred. [25][26][27][28] Other than the strong exciton-phonon interaction, the excitation photon energies used for the PL measurements in our case here ($6.28 emission intensities of the phonon-assisted lines due to the resonant Raman scattering process.…”
mentioning
confidence: 99%
“…Values of 6.5 meV and 6.4 meV for the E 2g mode phonon energy of low frequency have been previously deduced, respectively, from a theoretical calculation and Raman scattering experiment. 25,30 This phonon, related to the two BN planes slide against each other, has been termed as a "rigidlayer shear mode." 30 From the relative emission intensities, the 5.763 eV (S4t) and 5.791 eV (S3t) emission lines are, respectively, one phonon replicas (emitting one E 2g phonon of 8 meV) of the 5.771 eV (S4) and 5.799 eV (S3) emission lines.…”
mentioning
confidence: 99%
See 1 more Smart Citation